2020
DOI: 10.3390/molecules25030757
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Inhibits Cell Survival and Metastatic Ability via the EMT-Mediated Pathway in Oral Squamous Cell Carcinoma

Abstract: This study aimed to investigate whether quercetin exerts anticancer effects on oral squamous cell carcinoma (OSCC) cell lines and to elucidate its mechanism of action. These anticancer effects in OSCC cells were assessed using an MTT assay, flow cytometry (to assess the cell cycle), wound-healing assay, invasion assay, Western blot analysis, gelatin zymography, and immunofluorescence. To investigate whether quercetin also inhibits transforming growth factor β1 (TGF-β1)-induced epithelial-mesenchymal transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…Considering the scarce data on chemical composition of P. amphibia [34,35,42,47] this work, with quantitative and tentative qualitative HPLC analysis, creates a notable contribution. cycle arrest [56][57][58]. Thus, quercetin caused the cell cycle arrest in G2/M phase, which was followed by a decrease in cell numbers in the G0/G1 phase [58].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the scarce data on chemical composition of P. amphibia [34,35,42,47] this work, with quantitative and tentative qualitative HPLC analysis, creates a notable contribution. cycle arrest [56][57][58]. Thus, quercetin caused the cell cycle arrest in G2/M phase, which was followed by a decrease in cell numbers in the G0/G1 phase [58].…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted on cell lines of neoplasms affecting the area of head and neck showed that these cells are sensitive to quercetin, and the sensitivity depends on the cell line, exposure time and quercetin concentration. It was demonstrated that is cytotoxically affects the following cell lines of the tongue cancer: SAS [ 51 , 52 , 53 , 54 ], OSC20 [ 52 ], SCC25 [ 48 , 55 , 56 ], SCC-9 [ 57 ], HSC-3 [ 58 , 59 ], Tca8113 [ 49 , 54 ], SCC-15 [ 49 ], TW206 [ 58 ]; throat cancer: FaDu line [ 59 ]; oral cavity cancer: HN22 [ 52 ] and TW206 [ 58 ] lines.…”
Section: Anticancer Potential Of Flavonolsmentioning
confidence: 99%
“…Inducing an inhibition of a cell cycle and apoptosis are well-known methods for treating some types of cancer. It was demonstrated that quercetin causes an increase in the percentage of cells in the G2/M phase of the cell cycle and a decrease in the percentage of cells in the G0/G1 phase [ 52 , 58 ]. After a treatment involving various doses of quercetin (25–75 μM), the percentage of cells in the G1 phase increases with a simultaneous decrease in the number of cells in the S phase and a gradual increase in the percentage of cells in the G1 phase with simultaneous increases in the cells in the sub-G phase, which indicates induction of apoptosis ( Figure 5 ) [ 55 ].…”
Section: Anticancer Potential Of Flavonolsmentioning
confidence: 99%
See 2 more Smart Citations